2014
DOI: 10.1103/physrevb.89.104426
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between localized and itinerant magnetism in Co-substituted FeGa3

Abstract: The evolution of the electronic structure and magnetic properties with Co substitution for Fe in the solid solution Fe1−xCoxGa3 was studied by means of electrical resistivity, magnetization, ab initio band structure calculations, and nuclear spin-lattice relaxation 1/T1 of the 69,71 Ga nuclei. Temperature dependencies of the electrical resistivity reveal that the evolution from the semiconducting to the metallic state in the Fe1−xCoxGa3 system occurs at 0.025 < x < 0.075. The 69,71 (1/T1) was studied as a func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Large Co doping induces substantial disorder as reflected by the line broadening of the 69,71 Ga Nuclear Quadrupole Resonance (NQR) spectra and by the deviation of the lattice parameters from Vegard's law 17 . Fe 1−x Co x Ga 3 remains paramagnetic for all Co concentrations investigated 11 , while showing a complex magnetic behavior including itinerant and localized moment character and strong antiferromagnetic (AFM) spin fluctuations for Co substitution close to 0.5 18 .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Large Co doping induces substantial disorder as reflected by the line broadening of the 69,71 Ga Nuclear Quadrupole Resonance (NQR) spectra and by the deviation of the lattice parameters from Vegard's law 17 . Fe 1−x Co x Ga 3 remains paramagnetic for all Co concentrations investigated 11 , while showing a complex magnetic behavior including itinerant and localized moment character and strong antiferromagnetic (AFM) spin fluctuations for Co substitution close to 0.5 18 .…”
Section: Introductionmentioning
confidence: 94%
“…A recent example is the electron doping of the intermetallic FeGa 3 that leads to enhanced thermoelectric figures of merit [2][3][4][5][6][7][8][9][10] and to emergent magnetic behavior accompanied by the possible observation of a Ferromagnetic Quantum Critical Point (FMQCP) [11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent nuclear spin-lattice relaxation study for FeGa 3 unambiguously proved the existence of in-gap states located just below the bottom of the conduction band [46]. The number of these states estimated from the Hall constant [32] is ∼1.6×10 16 cm −3 , which is much larger than typical impurity levels observed in intrinsic band semiconductors (e.g., Si, Ge) and even in correlated band insulators (e.g., FeSi, FeSb 2 ) [46]. Measurements of the Hall effect performed by Hadano et al [32] indicated that in region III mobility of carriers decreases strongly with increasing temperature (μ ∼ T −5/2 ), whereas the number of carriers remains nearly unchanged.…”
Section: A Fegamentioning
confidence: 99%
“…For FeGa 3 , electron-type doping induces a crossover to a correlated metallic state at x ≈ 0.05 and y ≈ 0.006 in Fe 1−x Co x Ga 3 [34] and FeGa 3−y Ge y [35], respectively. Interestingly, further doping with Ge in FeGa 3−y Ge y leads to a ferromagnetic quantum critical point at x ≈ 0.016-0.05 [35,37], whereas for Fe 0.5 Co 0.5 Ga 3 nuclear spin-lattice relaxation measurements revealed a very fast relaxation with temperature dependence 1/T 1 ∝ T 1/2 being a unique feature of weakly and nearly antiferromagnetic metals [46]. A recent computational study suggested the formation of an itinerant ferromagnetic state with half-metallic properties in FeGa 3 in case of doping with both electrons and holes [43].…”
Section: Introductionmentioning
confidence: 99%